1984
DOI: 10.1149/1.2115632
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Redox Formal Potentials Accompanying the Incorporation of Cationic Complexes in Perfluoro Polycarboxylate and Polysulfonate Coatings on Graphite Electrodes

Abstract: The formal potentials of several redox couples incorporated in coatings of a perfluoropolycarboxylate on graphite electrodes were measured and compared with the formal potentials of the same couples in homogeneous solution. The differences observed agreed with those calculated from the Nernst equation with the independently measured incorporation coefficients for both halves of the redox couples. The dependences of the shifts in formal potentials on the nature of the incorporating complex ion, the ionic streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…contrast to the usually straightforward voltammetry of this compound (37). Such behavior has been previously reported (29,38,39) and was attributed to interactions of ionic redox couples with polyelectrolyte films (40). In this case it appears that the amine group of DHBA is the cause of the observed behavior.…”
Section: Resultssupporting
confidence: 46%
“…contrast to the usually straightforward voltammetry of this compound (37). Such behavior has been previously reported (29,38,39) and was attributed to interactions of ionic redox couples with polyelectrolyte films (40). In this case it appears that the amine group of DHBA is the cause of the observed behavior.…”
Section: Resultssupporting
confidence: 46%
“…The hydrophilic and hydrophobic domains in the Nafion film are in close proximity, 1a-c and hence both hydrophilic and hydrophobic interactions play an important role in determining the relative stability of the electroactive ions in Nafion film . It has been found that the interaction of the incorporated molecules with the hydrophobic region of the Nafion film influenced the formal potentials of metal complexes . In the case of phenothiazine dyes, the hydrophobicity of the reduced dye molecules played a major role in determining the electrochemical properties of these molecules in Nafion film.…”
Section: Resultsmentioning
confidence: 99%
“…The smaller (apparent) diffusion coefficients derived from Levich plots confirm slower diffusion/reduced availability of the ferrocyanide upon polymer addition (Supporting Information Figure S11). More importantly, the voltammograms shift towards more negative potentials upon addition of the polyelectrolytes, due to the preferred interaction of the quaternized units with the ferri- and not the ferrocyanide (Figure 2b) [35]. Hence, the oxidation of ferro- to ferricyanide strengthens the interaction pattern of these two oppositely charged components in solutions of hexacyanoferrates and the corresponding quaternized polymeric sites.…”
Section: Resultsmentioning
confidence: 99%